CAROTENOID EXTRACTION OF ORANGE-FLESHED SWEET POTATO AND ITS APPLICATION AS NATURAL FOOD COLORANT [Ekstraksi Karotenoid Ubi Jalar Jingga dan Aplikasinya sebagai Pewarna Makanan Alami] - Erliana Ginting (Jurnal Teknologi dan Industri Pangan, 2013)
The orange-fleshed sweet potato is rich in carotenoids, which can potentially be used as a natural food colorant. However, effective and safe extraction techniques are needed. The carotenoid extraction of deep orange-fleshed cultivar (Beta 1) at different moisture contents of fresh tubers using combined solvents was studied. The research design was a factorial randomized complete design with two factors and three replicates. The first factor was moisture content of the grated tubers. The second factor was the ratios of ethanol and acetone. The extract obtained from the most effective extraction process was stored for 1 month at room temperature and also applied as a topping colorant for steamed cakes (bolu kukus) which was compared to bolu kukus treated with no colorant and with artificial yellow colorant. The results showed that the fresh tubers contained high moisture (79.28%) and beta-carotene (12,169 µg/100 g wb) with the lightness value (L*) of 44.77. Extraction of reduced-water grated-tubers (m.c. 60.63%) using ethanol-acetone at ratio of 5:5 v/v gave the highest content of beta-carotene in the extract (235.94 µg/ml) with L* value of 52.48. Meanwhile, fresh grated tuber extracted with ethanol-acetone (9:1 v/v) had the lowest beta-carotene content (12.49 µg/ml). The extract stored in a dark bottle for 1 month showed better color stability with higher beta-carotene content (92.18 µg/ml) than that of transparent bottle (20.12 µg/ml). The color, odor and taste of steamed cakes with the extract as a topping colorant were slightly liked by panelists and were similarly scored to those of the counterparts, yet had better odor acceptance.